Determination of lead (Pb) in local cosmetic products by atomic absorption spectroscopy - Rahmat, Amirah Che (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2011)
Cosmetic products have been extensively used for the purpose of personal hygiene, to improve self-esteem, prevent aging and help people to enjoy a full and rewarding life. However, these products can be harmful to human as it may contain heavy metals which have been included during the manufacturing process. Many are unaware about the effects of heavy metals in cosmetic products, especially when the cosmetic brands are only well-known among locals. Lead, for instance is believed to be used as color additive in cosmetic products. The aim of this study is to determine the concentration of lead (Pb) in cosmetic products available locally. Ten different brands of local cosmetic creams were selected and digested by using microwave digestion system for sample pre-treatment. The samples were analyzed by Graphite Furnace Atomic Absorption Spectroscopy (GF-AAS) for estimation of lead concentration in each. The feasibility of microwave digestion was determined by spike recovery method. The mean recoveries for spiked levels ranged between 90 to 96%. Results showed that the local cosmetic creams which have a strong vibrant color are indicative of higher lead concentration. Results also demonstrated that the concentrations of lead in tested creams are in the range of 0.62 to 67.5 μg/g. Of ten samples analyzed, none has contained concentration of lead higher than that of permitted in food by United States Food and Drug Association (US FDA) and The Malaysia Cosmetic Guidelines and ASEAN Cosmetic Directive.